2022
DOI: 10.3390/genes13122384
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Promotes Larval Metamorphosis of Mytilus coruscus

Abstract: Metamorphosis is a critical process in the transition from planktonic life to benthic life for marine invertebrates, which is accompanied by a large amount of energy consumption. Previous studies have proved that AMP-activated protein kinase (AMPK), as a vital energy regulator, plays a prominent role in mediating the growth and development of terrestrial animals. However, its function in the growth and development of marine invertebrates, especially in metamorphosis, remains elusive. This study explored the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recently, more and more studies have indicated that AMPK signaling is vital to the larval settlement and metamorphosis in marine invertebrates including the mussel Mytilus coruscus [ 29 ] and the barnacle Amphibalanus amphitrite [ 30 ], however, the underlying molecular mechanisms are unclear. To further elucidate the biochemical mechanisms by which AMPK regulates the larval settlement of M. sallei , we conducted a yeast two hybrid (Y2H) assay to identify its interacting proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, more and more studies have indicated that AMPK signaling is vital to the larval settlement and metamorphosis in marine invertebrates including the mussel Mytilus coruscus [ 29 ] and the barnacle Amphibalanus amphitrite [ 30 ], however, the underlying molecular mechanisms are unclear. To further elucidate the biochemical mechanisms by which AMPK regulates the larval settlement of M. sallei , we conducted a yeast two hybrid (Y2H) assay to identify its interacting proteins.…”
Section: Resultsmentioning
confidence: 99%